NEURON and Python - Hines, Michael; Davison, Andrew P.; Muller, Eilif (Frontiers in Neuroinformatics, 2009)
The NEURON simulation program now allows Python to be used, alone or in combination with NEURON's traditional Hoc interpreter. Adding Python to NEURON has the immediate benefit of making available a very extensive suite of analysis tools written for engineering and science. It also catalyzes NEURON software development by offering users a modern programming tool that is recognized for its flexibility and power to create and maintain complex programs. At the same time, nothing is lost because all existing models written in Hoc, including GUI tools, continue to work without change and are also available within the Python context. An example of the benefits of Python availability is the use of the XML module in implementing NEURON's Import3D and CellBuild tools to read MorphML and NeuroML model specifications.